Magnifying endoscopy with narrow‐band imaging for diagnosis of subtype of gastric intestinal metaplasia. Issue 1 (8th November 2022) - Kanemitsu, Takao; Uedo, Noriya; Ono, Takahiro; Nimura, Satoshi; Hasegawa, Rino; Imamura, Kentaro; Ohtsu, Kensei; Ono, Yoichiro; Miyaoka, Masaki; Ueki, Toshiharu; Tanabe, Hiroshi; Ohta, Atsuko; et al.
Abstract: Background and Aim: Patients with incomplete gastric intestinal metaplasia (GIM) have a higher risk of gastric cancer (GC) than those with complete GIM. We aimed to clarify whether micromucosal patterns of GIM in magnifying endoscopy with narrow‐band imaging (M‐NBI) were useful for diagnosis of incomplete GIM. Methods: We enrolled patients with a history of endoscopic resection of GC or detailed inspection for suspicious or definite GC. The antrum greater curvature and corpus lesser curvature were regions of interest. Areas with endoscopic findings of light blue crest and/or white opaque substance (WOS) were defined as endoscopic GIM, and subsequent M‐NBI was applied. Micromucosal patterns were classified into Foveola and Groove types, and targeted biopsies were performed on GIM with each pattern. GIM was classified into complete and incomplete types using mucin (MUC)2, MUC5AC, MUC6, and CD10 immunohistochemical staining. The primary endpoint was the association between micromucosal pattern and histological subtype. The secondary endpoint was endoscopic findings associated with incomplete GIM. Results: We analyzed 98 patients with 156 GIMs. Univariate analysis (odds ratio [OR] 3.4, P  = 0.004), but not multivariate analysis (OR 0.87, P  = 0.822), demonstrated a significant association between micromucosal pattern and subtype. The antrum (OR 3.7, P  = 0.006) and WOS (OR 43, P  = 0.002) were independent predictors for incomplete GIM. The WOS had 69% sensitivity and 93% specificity. Conclusions: The M‐NBI micromucosal pattern is not useful for diagnosis of GIM subtype. WOS is a promising endoscopic indicator for diagnosis of incomplete GIM. (UMIN‐CTR000041119).